Did the periodic intensification of routine immunisation strategy (Intensified mission Indradhanush) reduce the demand for pediatric antibiotic formulations in India? - Habib Hasan Farooqui (7861166) (2025)
Background Recent research has indicated an increase in antibiotic utilisation, particularly pediatric formulations. Furthermore, an increasing trend in antimicrobial resistance rates has also been reported. Empirical evidence suggests that immunisation reduces the demand for antibiotics. We examined the potential impact of the periodic intensification of the routine immunisation strategy - Intensified Mission Indradhanush (IMI), which was implemented from October 2017 to January 2018, on antibiotic utilisation in India. Methods We analysed the PharmaTrac dataset to assess the impact of IMI on antibiotic utilisation. We conducted interrupted time series analyses by fitting a Poisson regression model. We used Newey–West standard errors to account for autocorrelation and heteroskedasticity. Findings Poisson segmented regression analysis showed a 12.6% decrease in Fluoroquinolones sales in the first month of IMI implementation (incidence rate ratio [IRR] 0.874, 95%CI: 0.777–0.983). However, post-intervention, their sales remained broadly constant (IRR 1.000, 95%CI 0.995–1.006). Similarly, Chloramphenicol sales decreased by 0.6% in the first month, whereas sales increased by a trend of 0.4% per month (IRR 1.004, 95%CI 0.991–1.017) post-intervention. Interestingly, Trimethoprim sales increased by 17.1% in the first month but decreased by 0.4% per month (IRR 0.959, 95%CI 0.945–0.973) post-intervention. However, there was a modest increase in sales of Macrolides by 3.0%, Cephalosporins by 2.9% and broad-spectrum Penicillin by 0.2% in the first month. Thereafter, Macrolides sales increased by a monthly rate of 0.5% (IRR 1.005, 95% CI 1.000–1.010), Cephalosporins increased by 0.5% (IRR 1.005, 95% CI 1.000 -1.010) and Broad spectrum penicillin increased by 0.9% (IRR 1.009, 95% CI 1.004–1.013) in the post-intervention period. Furthermore, there were heterogeneities across Indian states. Interpretation The IMI’s impact on antibiotic utilisation was heterogeneous across antibiotic classes and Indian states. Other Information Published in: BMC Infectious Diseases License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12879-025-11082-3